Abre los ojos and vanilla sky: a verbal and visual analysis of two conversations between the main characters - Gamberalli, Sheila Kath (2012)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-graduação em Letras/Inglês e Literatura Correspondente, Florianópolis, 2012.